Gait and balance dysfunction are associated with cognitive performance only in men with Parkinson’s disease - Amy W. Amara; Kimberly H. Wood; Aya M. Miften; Lina Kleinschmidt; Corey S. White; Allen Joop; Raima A. Memon; Jennifer Pilkington; Jutaluk Kongsuk; Corina Catiul; Adeel A. Memon; Marcas M. Bamman; et al. (Clinical Parkinsonism & Related Disorders)
Introduction: Parkinson’s disease (PD) can cause locomotor dysfunction and cognitive impairment and these symptoms are often associated. This study assesses relationships between comprehensive cognitive performance and locomotor function domains: gait, balance, and mobility, in men and women with PD. Methods: Sixty PD participants, Hoehn and Yahr 1–3, age ≥ 45, and Montreal Cognitive Assessment score ≥ 18, underwent locomotor function assessments and a comprehensive neurocognitive battery. Primary outcomes included Timed Up and Go (TUG), maximum walking speed (MWS), Mini Balance Evaluation Systems Test (Mini-BESTest), and cognitive composite score (CCS). Spearman correlations determined associations between cognition and locomotor function for the total sample and separately for men and women. Results: CCS correlated with all primary locomotor outcomes for the overall group and men only. Specifically, positive relationships were observed between the CCS and Mini-BEST Test (balance) for the overall group (p = 0.009) and men (p = 0.001), as well as MWS (gait) for the overall group (p = 0.006) and men (p < 0.001). CCS and TUG (mobility) were negatively correlated for the overall group (p = 0.005) and men (p < 0.001). There were no significant correlations between CCS and locomotor outcomes in women. Exploratory analyses suggest that performance in executive function, visuospatial skills, and processing speed drive these relationships. Conclusion: In PD, balance, gait, and mobility correlated with global cognition. Correlations between motor function and cognitive performance were evident only in men. This study enhances understanding of the complex interplay between cognition and motor function in PD, especially among men.